Changing access to ice, land and water in Arctic communities - Ford, J D; Clark, D; Pearce, T; Berrang-Ford, L; Copland, L; Dawson, J; New, M; Harper, S L (Nature Climate Change, 2019)
Arctic climate change has the potential to affect access to semi-permanent trails on land, water and sea ice, which are the main forms of transport for communities in many circumpolar regions. Focusing on Inuit Nunangat (the Inuit homeland in northern Canada), trail access models were developed drawing upon a participatory process that connects Indigenous knowledge and science. We identified general thresholds for weather and sea ice variables that define boundaries that determine trail access, then applied these thresholds to instrumental data on weather and sea ice conditions to model daily trail accessibility from 1985 to 2016 for 16 communities. We find that overall trail access has been minimally affected by >2 °C warming in the past three decades, increasing by 1.38–1.96 days, differing by trail type. Across models, the knowledge, equipment and risk tolerance of trail users were substantially more influential in determining trail access than changing climatic conditions.